1997
DOI: 10.1001/archinte.1997.00440320040005
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein Lp(a) Excess and Coronary Heart Disease

Abstract: Lipoprotein Lp(a) excess has been identified as a powerful predictor of premature atherosclerotic vascular disease in several large, prospective studies. Lipoprotein Lp(a) levels modulate the risk of coronary heart disease in patients with hypercholesterolemia, and lipoprotein Lp(a) excess is commonly detected in men and women with premature coronary atherosclerosis. Lipoprotein Lp(a) contributes to atherothrombotic risk by multiple mechanisms that include impaired fibrinolysis, increased cholesterol depositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
54
0
2

Year Published

1997
1997
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(57 citation statements)
references
References 114 publications
1
54
0
2
Order By: Relevance
“…Of note, in subgroup analyses, we found that Lp(a) in the subgroup of nondiabetic patients using statins was not associated with vascular events, whereas it was strongly predictive of vascular events in nondiabetic patients who did not receive statins. Although statins do not considerably influence Lp(a) serum values, they very effectively lower LDL cholesterol [43]. Lp(a) is less strongly associated with vascular events when LDL cholesterol is low, and lowering LDL with statins might be an effective approach at decreasing the cardiovascular risk conferred by high Lp(a) [44].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, in subgroup analyses, we found that Lp(a) in the subgroup of nondiabetic patients using statins was not associated with vascular events, whereas it was strongly predictive of vascular events in nondiabetic patients who did not receive statins. Although statins do not considerably influence Lp(a) serum values, they very effectively lower LDL cholesterol [43]. Lp(a) is less strongly associated with vascular events when LDL cholesterol is low, and lowering LDL with statins might be an effective approach at decreasing the cardiovascular risk conferred by high Lp(a) [44].…”
Section: Discussionmentioning
confidence: 99%
“…By inhibiting fibrinolysis, increased levels of lipoprotein(a) potentially delay thrombolysis and contribute to plaque progression [87]. There is also an impaired attenuation of clot formation and fibrinolysis in the diabetic state [82][83][84][85][86][87][88][89].…”
Section: Coagulation Abnormalities In Diabetesmentioning
confidence: 99%
“…4 Elevated Lp(a) levels have been considered a risk factor for coronary and peripheral artery diseases. [5][6][7] However, one recent study failed to demonstrate an association between elevated Lp(a) levels and the risk of coronary artery disease in women aged Ն 55 years, 8 thus raising some doubt about the universal applicability of the results of previous studies that were mainly based on male and middle-aged subjects. [9][10][11][12][13][14][15][16][17][18][19][20] The role of elevated Lp(a) levels as a risk factor for cerebrovascular diseases is controversial.…”
mentioning
confidence: 99%